Importance Understanding Rights and Obligations Citizens in Election Head of Medan City District 2020 - Nasution, Faiz Albar; Thamrin, Muhammad Husni; Nasution, Muhammad Arifin; Adela, Fernanda Putra; Bahri, Saipul (Talenta Publisher, 2020)
Participation of citizens in using voting rights as a key element to success of Election. However, voter participation in Medan regional elections since reforms until now, tends experience a low participation rate. Thus, political socialization education is important, in order to maintain quantity and quality in the 2020 Medan City Head Election. The objectives of this activity include: First, disseminating information about the stages, schedule and objectives of the election. Second, increase citizens' knowledge and awareness of rights and obligations in elections. Third, increase voter participation in elections. Method of socialization through lectures and discussions from speakers to activity participants by applying strict health protocols.. The results of socialization activities show the enthusiastic attitude of the Community of the Sovereign People's Movement of North Sumatra in participating in this activity. Socialization participants argue that this activity can increase their knowledge of the rights and obligations of citizens ahead of the Election. Evidently, socialization participants are committed to participate in inviting the people of Medan to participate and follow the entire process of the simultaneous election stage 2020.